Project manager's perception of the local communities' stakeholder in megaprojects. An empirical investigation in the UK. Issue 3 (April 2018) - Di Maddaloni, Francesco; Davis, Kate
Abstract: Based on an exploratory study conducted in the UK using thematic and cluster analysis, this paper investigates how the local communities' stakeholder is perceived, defined and categorized by project managers in major public infrastructure and construction projects (MPIC), and how their involvement could improve the performance of these projects. Due to the perceived benefits shortfall of MPIC, well organized actions from 'secondary stakeholder' groups have led to delays, cost overruns, and significant damage to the organization's reputation. Stakeholder management is an essential process which aims to maximize positive inputs and minimize detrimental attitudes by taking into account the needs and requirements of all project stakeholders. However, current project stakeholder management mechanisms are reactive rather than proactive, mainly offering an instrumental perspective, which aims to make the stakeholders comply with project needs. Therefore, a broader inclusiveness of secondary stakeholders who could be harmed by the organization's strategy, such as the local communities, is required to enhance the performance of MPIC. Highlights: To explore secondary stakeholders in major public infrastructure and construction projects (MPIC). To investigate project manager's perception, identification and categorization of the local communities' stakeholder. To enhance current stakeholder management practices at the local level of MPIC to improve project performance.